Подродовая систематика песчанок рода Tatera Lataste, 1882 в связи с особенностями строения их костного среднего уха - Павлинов, И.Я. (Вестник зоологии, 1981)
Three types of the mastoideum morphology and two types of the malleus morphology are revealed in the Tatera genus. Three groups of species are distinguished which are considered as separate subgenera: monotypic Tatera s. str. and Gerbilliscus and polytypic Taterona.